SERVQUAL Method in Assessing the Quality of Rural Tourism Services - Миронов Юрій Богданович; Kudla Nazar (USAMV Bucharest, 2020)
The main supply factors at the rural tourism services market (on the example of rural tourism households of the Transcarpathian region of Ukraine) are characterized. The SERVQUAL method has been modified taking into account the usage of certain elements and assessment principles of the most important criteria for the rural agritourism services quality. A marketing research of the proposed rural tourism products with a comparison of the expected and perceived quality of the tourist product was conducted. The rural tourism services quality assessment depends primarily on the personal perception of tourists during their stay at rural tourism households and is assessed through the prism of hospitality, competence, propensity to provide qualitative tourist services, family atmosphere, obscenity with tourists' needs and ability to meet safety and security, willingness to respond to guests’ complaints.
Keywords: rural tourism; services quality; SERVQUAL method; consumer satisfaction; rural tourism product; rural agritourism household